Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1109/tmag.2018.2827923
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-Plane Auto-Oscillation in Spin Hall Oscillator With Additional Polarizer

Abstract: The theoretical investigation on magnetization dynamics excited by the spin Hall effect in metallic multilayers having two ferromagnets is discussed. The relaxation of the transverse spin in one ferromagnet enables us to manipulate the direction of the spin-transfer torque excited in another ferromagnet, although the spin-polarization originally generated by the spin Hall effect is geometrically fixed. Solving the Landau-Lifshitz-Gilbert-Slonczewski equation, the possibility to excite an out-of-plane auto-osci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 45 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…Here, G is the Gaussian random number generator vector of the STNO with components (G x , G y , G z ), which satisfies the statistical properties < G m (t) >= 0 and < G m (t)G n (t ′ ) >= δ mn δ(t − t ′ ) for all m, n = x, y, z. k B is the Boltzmann constant, T is the temperature, V is the volume of the free layer, △t is the step size of the time scale used in the simulation and µ 0 is the magnetic permeability at free space. The material parameters for the investigations are considered as γ = 1.764 × 10 7 rad/(Oe s), K = 18.6 kOe, M s = 1448.3 emu/c.c., α = 0.005, θ sh = 0.1, d = 1 nm and V = π × 50 × 50 × 1 nm 3 [25,26,38,43].…”
Section: Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, G is the Gaussian random number generator vector of the STNO with components (G x , G y , G z ), which satisfies the statistical properties < G m (t) >= 0 and < G m (t)G n (t ′ ) >= δ mn δ(t − t ′ ) for all m, n = x, y, z. k B is the Boltzmann constant, T is the temperature, V is the volume of the free layer, △t is the step size of the time scale used in the simulation and µ 0 is the magnetic permeability at free space. The material parameters for the investigations are considered as γ = 1.764 × 10 7 rad/(Oe s), K = 18.6 kOe, M s = 1448.3 emu/c.c., α = 0.005, θ sh = 0.1, d = 1 nm and V = π × 50 × 50 × 1 nm 3 [25,26,38,43].…”
Section: Modelmentioning
confidence: 99%
“…[18,19,20]. Further, spin-Hall oscillations and synchronization in spin-Hall oscillators have also been widely studied both theoretically and experimentally [21,22,23,24,25,26,27,28]. Particularly, Liu et al have observed the SHE driven magnetization oscillations with frequency around 1.6 GHz in magnetic tunnel junction that consists of in-plane magnetized free layer of 1.5 nm thickness in the presence of external magnetic field [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies on magnetization switching and steady state precession are reported and the threshold current formula was derived for the switching of a perpendicular magnetization by the SHE in references [18][19][20]. Further, spin-Hall oscillations and synchronization in spin-Hall oscillators have also been widely studied both theoretically and experimentally [21][22][23][24][25][26][27][28]. Particularly, Liu et al have observed the SHE driven magnetization oscillations with frequency around 1.6 GHz in magnetic tunnel junction that consists of in-plane magnetized free layer of 1.5 nm thickness in the presence of external magnetic field [27].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, Liu et al have observed the SHE driven magnetization oscillations with frequency around 1.6 GHz in magnetic tunnel junction that consists of in-plane magnetized free layer of 1.5 nm thickness in the presence of external magnetic field [27]. It has been shown that the magnetization oscillations are possible in the spin-Hall system when placing an additional tilted polarizer [29][30][31][32][33] above or below the ferromagnetic layer along with a spacer [25,26]. The SHE has been utilized for self-oscillations in an in-plane magnetized system under the effect of applied magnetic field [27].…”
Section: Introductionmentioning
confidence: 99%